Studying horror cinema - Turnock, Bryan (Studying films., 2019)
Aimed at teachers and students new to the subject, this book is a comprehensive survey of the horror film genre from silent cinema to its twenty-first century resurgence. Structured as a series of thirteen case studies of easily accessible films, it covers the historical, production, and cultural context of each film, together with detailed textual analysis of key sequences. Sitting alongside such acknowledged classics as Psycho and Rosemary's Baby are analyses of influential non-English language films as Kwaidan, Bay of Blood, and Let the Right One In. The author concludes with a chapter on 2017's blockbuster It, the most financially successful horror film of all time.